2020
DOI: 10.1371/journal.pone.0235960
|View full text |Cite|
|
Sign up to set email alerts
|

Functional mechanism of AMPK activation in mitochondrial regeneration of rat peritoneal macrophages mediated by uremic serum

Abstract: Objective To investigate the effects of AMPK activation on mitochondrial inhibition by uremic serum through the AMPK-activated rat peritoneal macrophages stimulated by uremic serum, thereby providing a reference for the clinical treatment of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Specifically, the overall concept, objectives, study design, and methodology of this article [ 1 ] are similar to work reported in previously published Master’s theses [ 2 , 3 ] and a published article [ 4 ]. The experimental design and results reported in all figures and tables of [ 1 ] appear very similar to those previously reported in [ 2 , 3 ], though the individual data values reported are not identical.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Specifically, the overall concept, objectives, study design, and methodology of this article [ 1 ] are similar to work reported in previously published Master’s theses [ 2 , 3 ] and a published article [ 4 ]. The experimental design and results reported in all figures and tables of [ 1 ] appear very similar to those previously reported in [ 2 , 3 ], though the individual data values reported are not identical.…”
mentioning
confidence: 70%
“…After this article [ 1 ] was published, concerns were raised regarding the similarity to previous works [ 2 – 4 ] by different authors and that were not cited in [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The heatmap was analyzed using an online server Heatmapper ( www.heatmapper.ca/expression/ ). Rat peritoneal macrophages (RPMs) were isolated and cultured as described previously ( Chen et al, 2020 ). RPMs grown in 12-well plates (5 × 10 5 cells/well) were treated by LPS (10 ng/mL) plus soluble cholesterol (CHO; 100 μg/mL) with or without the presence of Art (20 μg/mL) for 1 h ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Rat peritoneal macrophages (PMs) were isolated as described previously [47]. In brief, animals were intraperitoneally injected with ice-cold PBS and peritoneal fluid was aspirated and centrifuged at 300 g for 5 min.…”
Section: Peritoneal Macrophage Culturementioning
confidence: 99%